Strategies to Overcome Barriers and Strengthen Support for Cadre Education Management in Muhammadiyah Collage - Sarli Amri Teguh Pribadi; Agus Suradika; Oneng Nurul Bariyah (Yayasan Adra Karima Hubbi, 2024)
Background. Muhammadiyah universities have not been able to carry out good management in solving the problem of regeneration activities. This includes fostering the regeneration of ortoms and education personnel in Muhammadiyah universities in order to produce superior Muhammadiyah cadre candidates for the future. Purpose. This research aims to analyse in depth the form of cadre activities and the management of the cadre education implementation process at the Muhammadiyah Center of Excellence in Banten Province as well as strategies to deal with inhibiting and supporting factors in cadre management. Method. In this study, researchers used a qualitative approach (Lexy J. Moleong, 2005: 4) based on phenomenological philosophy by prioritising appreciation(verstehen). Qualitative methods seek to understand and interpret the meaning of an event of human behaviour interaction in a particular situation according to the researcher's perspective (Husnaini, 1996: 81). Results. The form of cadre activities is carried out in 2 (two) forms including Primary Cadre through Baitul Arqom and Functional Cadre, namely through recitation, Governance / Upgrading Training, Ideopolitor Dialogue (Ideology, Politics and Organisation). Then the implementation of cadre education activities including through IPM (Muhammadiyah Student Association), HW (Hizbul Wathan) and TSPM (Tapak Suci Putera Muhammadiyah). Conclusion. The research can provide input on how the effectiveness of the cadre education management system can be more effective in producing quality cadres and improving the efficiency of cadre education management by examining the potentials that can be optimised in cadre education management.